Distance Makes the (Committed) Heart Grow Colder: MNEs' Responses to the State Logic in African Variants of CSR. Issue 3 (March 2018) - Reddy, Colin David; Hamann, Ralph
The question of how multinational enterprises (MNEs) respond to local corporate social responsibility (CSR) expectations remains salient, also in the context of many African governments' attempts to define and regulate business responsibilities. What determines whether MNEs respond to such local, state-driven expectations as congruent with their global commitment to CSR? Adopting an institutional logics perspective, we argue that a higher global CSR commitment will lead to higher local responsiveness when regulatory distance is low, but it will lead to lower local responsiveness when regulatory distance is high. We find support for our hypothesis using data on 93 MNEs' responses to the South African state's Broad-Based Black Economic Empowerment policy. We thus contribute to the global–local CSR literature and show how MNEs' local CSR responsiveness will be shaped by not only the local context but also their home country and firm-internal environments.